Thermal deformation behaviors, mechanisms, and microstructure evolution of laminate CNT/2009Al composite - P.Y. Li; X.N. Li; K. Ma; Z.Y. Liu; B.L. Xiao; Z.Y. Ma (Journal of Materials Research and Technology)
The plastic deformation mechanism of laminate CNT/2009Al composite during hot compression was investigated through isothermal compression tests conducted on coarse grain 2009Al, ultrafine grain 3 vol% CNT/2009Al, and the laminate composite. This study employed flow stress-strain curve analysis, processing map evaluation, and finite element modeling to characterize the isothermal compression deformation behavior of the laminate composite. The results indicated that the deformation coordination of the laminate composite was influenced by the evolution of microstructure and the stress-strain distribution between the CNT-rich and 2009Al layers. Specifically, better deformation coordination was observed between the two layers at a medium temperature with a moderate strain rate (450 °C-0.1 s−1). Moreover, there was a more pronounced occurrence of dynamic recrystallization and microstructure evolution at a high strain rate (450 °C-1 s−1) compared to a low strain rate (450 °C-0.001 s−1). In addition, when the temperature was changed, the plastic deformation and softening mechanisms changed.